Materiais para ortopedia contendo gálio na matriz da hidroxiapatita modificada pelo estrôncio e vanádio - Albuquerque, Diogo Muniz de (2021)
The modified hydroxyapatite through the introduction of bioactive elements gallium and strontium was obtained. Vanadatoapatite containing gallium was synthesized, its composition was confirmed and the physicochemical properties studied, in particular, the morphology and basic structural parameters. It was demonstrated that the gallium is homogeneously distributed in the structure in the form of solid intercalation solution without producing distortions in the hexagonal network of hydroxyapatite. Vanadatoapatite was also synthesized by replacing calcium with strontium and, at the same time, containing gallium as a doping element. Conditions for the preparation of the compost and its morphological and structural characteristics were established. It has been shown that in the case of vanadatoapatite with calcium, the dopant is evenly distributed in the form of a solid replacement solution. With regard to the position of the strontium, this, according to X-ray diffractometry, remains at the calcium ion sites, as a result of the isovalent substitution. It was evident that the structural characteristics of materials obtained that contain one or two bioactive elements in question, respond to the requirements of natural hydroxyapatite and, at the same time, to a material similar to the structure of human hydroxyapatite. It was demonstrated, through in vitro toxicity tests, that the composition containing gallium as a dopant meets the acceptability criteria in orthopedic procedures. The obtained structural parameters are available to be included in the international biomaterials databases, in particular for a future application in orthopedics.